Factors associated with non‐participation and dropout among cancer patients in a cluster‐randomised controlled trial. (30th January 2017) - Roick, J.; Danker, H.; Kersting, A.; Briest, S.; Dietrich, A.; Dietz, A.; Einenkel, J.; Papsdorf, K.; Lordick, F.; Meixensberger, J.; Mössner, J.; Niederwieser, D.; et al.
Abstract : We investigated the impact of demographic and disease related factors on non‐participation and dropout in a cluster‐randomised behavioural trial in cancer patients with measurements taken between hospitalisation and 6 months thereafter. The percentages of non‐participation and dropout were documented at each time point. Factors considered to be potentially related with non‐participation and dropout were as follows: age, sex, marital status, education, income, employment status, tumour site and stage of disease. Of 1, 338 eligible patients, 24% declined participation at baseline. Non‐participation was higher in older patients (Odds Ratio [OR] 2.1, CI: 0.6–0.9) and those with advanced disease (OR 2.0, CI: 0.1–1.3). Dropout by 6 months was 25%. Dropout was more frequent with increased age (OR 2.8, CI: 0.8–1.2), advanced disease (OR 3.0, CI: 1.0–1.2), being married (OR 2.4, CI 0.7–1.1) and less frequent with university education (OR 0.4, CI −1.3 to −0.8) and middle income (OR 0.4, CI −0.9 to −0.7). When planning clinical trials, it is important to be aware of patient groups at high risk of non‐participation or dropout, for example older patients or those with advanced disease. Trial designs should consider their special needs to increase their rate of participation.